Education on Successful Strategies for Preparing Human Resources in 2026 Towards Career Success and Business Sustainability - Primadi Candra Susanto; Yuliantini; Olfebri; Prasadja Ricardianto; Esti Liana; Irwan Chairuddin (Siber Nusantara Research, 2025)
This community service activity aims to improve public understanding of strategies for preparing high-quality human resources to face the challenges of the workforce and business development in 2026. The increasingly rapid changes in the business environment, influenced by technological advancement, digitalization, and growing global competition, require individuals to possess adequate competencies, adaptability, and innovative skills. This community service program was implemented through socialization activities, training sessions, and interactive discussions involving students, job seekers, and small and medium-sized business actors. The materials delivered included professional competency development, improvement of interpersonal skills, utilization of digital technology, as well as career planning and sustainable business development strategies. The results of the activity indicate an increase in participants’ understanding of the importance of continuous self-development and the ability to adapt to technological changes and the dynamics of the labor market. In addition, participants were able to identify various career opportunities and potential business development aligned with the growth of the digital economy. Through this activity, it is expected that the community will be better prepared to face future challenges, improve the quality of human resources, and support the achievement of career success and sustainable business development.